2005
DOI: 10.1002/ejoc.200500288
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooctyne and 4‐Cyclooctyn‐1‐ol – Versatile Building Blocks in Organic Synthesis

Abstract: The readily available and highly reactive title compounds represent versatile building blocks in organic synthesis. Recent examples of 1,3‐dipolar cycloadditions and Diels–Alder reactions and their applications are described. This microreview is especially devoted to cycloadducts formed between 1 and 2 and furans, and their transformations to give a variety of different classes of compounds, including derivatives of natural products. Here the conversion of oxanorbornadienes into bridged oxepines plays an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 117 publications
0
21
0
Order By: Relevance
“…A range of different synthetic procedures is known to obtain medium-sized cycloalkynes, as covered by several reviews [38]; Tochtermann [25]. In this paragraph, only the most relevant procedures will be covered.…”
Section: Synthetic Preparation Of Cycloalkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of different synthetic procedures is known to obtain medium-sized cycloalkynes, as covered by several reviews [38]; Tochtermann [25]. In this paragraph, only the most relevant procedures will be covered.…”
Section: Synthetic Preparation Of Cycloalkynesmentioning
confidence: 99%
“…2) cycloadditions, hydrogen transfer reactions, radical additions, and reactions with metal salts or complexes, are also known. For further information on this topic, the reader is referred to several earlier reviews [25,32].…”
Section: Reactions Of Cycloalkynesmentioning
confidence: 99%
“…Wittig and Krebs reported that smaller cycloalkyne rings were too unstable for isolation, but their transient formation could be indirectly ascertained by trapping of the cycloheptyne or cyclohexyne generated in situ with phenyl azide and isolation of the resulting triazole products. In subsequent years, other procedures for the preparation of cyclooctynes have been developed and a variety of 1,3‐dipolar cycloaddition and Diels–Alder reactions have been reported, as summarized recently 28…”
Section: Cycloaddition With Cyclooctynementioning
confidence: 99%
“…These molecules should provide one functional group with a high selectivity for the substrate surface. Promising candidates for such a high selectivity for Si(0 0 1) are cyclooctynes which are used as versatile building blocks in organic synthesis [6] and chemical biology [7]. Cyclooctyne (C 8 H 12 ) is characterized by a high ringstrain of approximately 0.4 eV due to its stiff triple bond [8].…”
Section: Introductionmentioning
confidence: 99%